Transformasi Digital UMKM Ritel dan Pengaruhnya terhadap Daya Saing di Era Ekonomi Digital: dfgg - Devina Fitri Damayanti; Amanda Laila Nurrachma; Dian Ayu Ariyanti; Athika Dewi Afrianti; Nindya Angelina; Rusdi Hidayat Nugroho (Business and Investment Review, 2026)
This study aims to describe the readiness, opportunities, and challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the retail sector in implementing digital transformation to enhance competitiveness in the digital economy era. Digital transformation has become an essential aspect of MSME development, particularly following the shift in consumer behavior from offline to online transactions during the pandemic. This research employs a descriptive qualitative approach through observations, in-depth interviews, and SWOT analysis to understand the current conditions of micro-scale retail MSMEs. The findings indicate that the digitalization efforts of retail MSMEs are still primarily focused on marketing activities, such as the use of online stores, social media, and e-commerce platforms. Digitalization has been shown to improve operational efficiency, expand market reach, and strengthen business sustainability. However, micro-scale retail MSMEs still face several obstacles, including low digital literacy, limited technological infrastructure, and unstructured management practices. In addition, an excessive focus on mastering technology often reduces attention to product innovation and customer service. Retail MSMEs possess significant internal strengths and external opportunities to enhance competitiveness, including the utilization of supporting technologies such as mobile-based Point of Sale (POS) applications. Overall, this study concludes that improving digital competence, resource readiness, and adaptability are key determinants of successful digital transformation for retail MSMEs amid the dynamics of the digital economy.